Reference Values of Thromboelastometry Parameters in Healthy Term Neonates Using NATEM in Cord Blood Samples - Alma Sulaj; Marina Tsaousi; Eleni Karapati; Abraham Pouliakis; Zoi Iliodromiti; Theodora Boutsikou; Serena Valsami; Nicoletta Iacovidou; Marianna Politou; Rozeta Sokou (MDPI AG, 2022)
Background: ROTEM assay has gained increasing acceptance as a method for rapid and specific coagulation pathway assessment. However, its use in the neonatal population remains limited since reference ranges have not yet been established. Aims: (1) to determine reference ranges for healthy term neonates of ROTEM parameters using non-activated assay (NATEM) in cord blood samples; (2) to assess whether delivery mode, gender, gestational age, birth weight and blood group (ABO and Rhesus) of the neonate, coagulation disorder and anticoagulant medication of the mother have an impact on NATEM parameters. Methods: NATEM assay was conducted in cord blood samples of 189 term neonates without any medical history. Results: Reference ranges (2.5th and 97.5th percentiles) are established for clotting time (CT), clot formation time (CFT), α-angle, clot amplitude at 5, 10 and 20 min (A5, A10, A20), maximum clot firmness (MCF), lysis index at 30 and 60 min (LI30, LI60, %) and maximum clot elasticity (MCE). Reference ranges for NATEM are CT 182-499 s, CFT 63-176 s, α-angle 58-78°, A5 28-52 mm, A10 37-61 mm, A20 42-66 mm, MCF 43-67 mm, LI30 97-100%, LI60 87-98% and MCE 75-203. Male neonates appear to be more hypocoagulable than females. Conclusions: We demonstrate reference ranges for healthy term neonates in NATEM assay that could be used as a reference group for future studies of neonates with an underlying pathology.